PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK KELAS XI IPA SMAN 1 2X11 ENAM LINGKUNG - Rahma Yani (Departemen Matematika, 2023)
— One of the goals of learning mathematics that is expected in high school is that student have good reasoning abilities.These abilities can be developed through learning mathematics. However, in reality students’ mathematical about reasoning are still low. One of the efforts that can be made to improve students’ mathematical ability reasoning is applying the problem based learning model in learning process. The purpose of study was to find out whether the mathematical abilitiy reasoning of students who studied with the problem based learning model were better than students who studied with the direct learning model in class XI IPA SMAN 1 2x11 Enam Lingkung. This type of research is quasi-experimental with a Statics Group Design. The population in this study were students of class XI IPA SMAN 1 2x11 Enam Lingkung. the sample selection waas carried out by random sampling technique, slected class XI IPA 1 as the experimental group and class XI IPA 2 as the control group. Based on the results of the research data analysis at the real level and P-value = 0,001 using the t test. It was found that the mathematical reasoning abilities of students who studied with the problem based learning model were the better than those who studied with direct learning models in class XI IPA SMAN 1 2x11 Enam Lingkung.Keywords —Problem Based Learning(PBL), Mathematical Reasoning Ability, Direct Learning